ChemInform Abstract: Copper‐Catalyzed or ‐Mediated C—H Bond Functionalizations Assisted by Bidentate Directing Groups. Issue 27 (16th June 2016) - Liu, Jidan; Chen, Guoshu; Tan, Ze
Abstract: Review: [55 refs.